Mecanismos de resolução em conflitos penais e a horizontalidade na aplicação de metodologias da justiça restaurativa no Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This research presents an analysis of the restorative justice model as a tool in the context of the prison system crisis. According to the 2024 Brazilian Public Security Yearbook, in absolute numbers, there were a total of 852,010 people deprived of their liberty in 2023. Brazil currently ranks third in the world in terms of prison population, behind only the United States and China, which highlights the urgent need to rethink public policies for the Brazilian prison system. Based on the ideas of democratizing access to justice and institutional innovations that promote citizenship, restorative justice emerges as a meritorious initiative within the Brazilian Judiciary System. The research suggests that mass incarceration is not the only response to violence, as restorative justice is proposed from the perspective of a criminal policy focused not only on conflict but also on consensus among the victim, the offender, and the community, creating a dialogue environment that allows the construction of a common restorative denominator. In light of this, the research sought to understand the institution of imprisonment in the context of criminology, through abolitionist and minimalist theories of criminal law. In other words, it aimed at a critical reflection on criminal conflicts based on the principles proposed by restorative justice and the dilemmas in its practical application.
Mechanisms for Resolving Criminal Conflicts and the Horizontality in the Application of Restorative Justice Methodologies in Brazil
Keywords: CIENCIAS SOCIAIS APLICADAS: DIREITO; Justiça Restaurativa; Sistema prisional; Democratização; Encarceramento massivo; Aplicação